"It's Just the Way I Learn!": Inclusion from the Perspective of a Student with Visual Impairment. (September 2018) - Gilbert, Danni
This article describes the inclusive experience of a student with visual impairment in secondary band settings. Information obtained from students with visual impairments who have experienced active participation in school music ensembles may provide much-needed insight into instructional strategies that could improve inclusion. Many music educators believe they lack adequate resources and training in including students with visual impairments. Therefore, a deeper understanding of the experience of participating in secondary performing ensembles from the viewpoints of students can help guide the efforts of those involved in their music education.